Reported prevalence of interprofessional conflict in Indian health care, training adequacy and patient safety consequences: a multi-state cross-sectional study - Amrita Sarkar; Sonal Dayama; Meet Chauhan; Medha Mathur; Mamta Gehlawat; Debjit Roy (Frontiers in Health Services, 2026)
Background Interprofessional conflict can compromise, teamwork, workforce stability, and patient safety particularly in overstretched public health systems in India. Although international literature highlights this issue, multi-state evidence from India involving different healthcare cadres remains limited. Methods A cross-sectional survey was conducted among healthcare professionals from Arunachal Pradesh, Rajasthan, Gujarat, and Telangana Data were collected using a validated 12-item questionnaire on a 5-point Likert scale. The survey assessed the prevalence of interprofessional conflict, its perceived impact on patient care and teamwork, and the gap between the adequacy and importance of conflict-management training. Role-based differences were examined using ANOVA, and associations were explored with Spearman's correlation. Results Mean age of 566 health care professionals (doctors (52.7%), nurses (35.7%), and interns (11.6%)) surveyed was 29.8 years. Interprofessional conflict was commonly reported (mean 3.70; 65% agreement). Participants indicated that conflict affected care quality (mean=3.60, SD = 1.23), increased workplace stress (mean=3.51,SD = 1.15), and hindered collaboration (mea n = 3.32, SD = 1.12). A notable training gap emerged between perceived adequacy (2.95) and importance (3.88), with a difference of 0.93 (Cohen's d = 0.78, p < 0.001). Nurses reported higher stress levels (F = 6.84, p = 0.001), while interns perceived lower training adequacy (F = 9.97, p < 0.001). Conflict scores showed moderate correlations with reported delays or errors in care ( ρ = 0.43–0.69). Conclusions Interprofessional conflict is common and serious in India's healthcare settings; nearly two-thirds of participants report that it occurs. The findings show this conflict is a systemic issue that compromises care quality, increases workplace stress, and weakens team collaboration. Moderate correlations between conflict and care delays or errors highlight its risks to patient safety. The study urges making structured, cadre-sensitive interprofessional conflict-management training a top systems-level priority to strengthen teamwork, workforce well-being, and patient outcomes in India's public health system.